Strategi Ekspansi Usaha UMKM dengan Pendekatan Metoda Hybrid SWOT Analisis dan AHP - Filia Hanum; Maryam Maryam; Susanti Susanti; Cut Rusmina; Rahmi Rahmi; Juwita Juwita; Fitriliana Fitriliana (Jurnal Serambi Engineering, 2023)
MSMEs play a significant role in driving Indonesia’s economic growth. MSMEs contribute up to 60.5 percent of GDP. Labour absorption achieved 96.9 percent of the total nationally. The impact of the recent global economic crisis and the Covid-19 pandemic has been the most significant impediment for MSMEs.This situation caused a huge drop in MSME income, and several went bankrupt. As a result, this study offers alternative strategic options based on hybrid method decision makers’ instruments, namely SWOT analysis and Process Hierarchy Analysis (AHP). Several draft strategies have been developed in order to enhance the number of optimal MSME firms. The decisions made include the necessity for MSMEs to develop into innovative activities with high economic added value by employing government support in the form of finance, business training opportunities, institutional improvement, and more profitable business laws. Furthermore, this aid is intended for building enterprises on online platforms in order to boost MSMEs’ future competitiveness. MSMEs must also optimize in order to create innovative economic opportunities. As a result, MSMEs must optimize their human resources in order to capitalize on its commercial prospects. These essential human resources are then enhanced so that they can run online-based businesses in the future.